A Anatomical Study of Fruits for Some Genera of Fabaceae Family Grown in Makhoul Mountain–Salah Al-Din – Iraq (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
The fruits of six species belonging to four genera of the Fabaceae family were studied. Wild species of dicotyledons that grow in the study area and in the foothills of Makhoul Mountain in Salah al-Din governorate were studied.  The fruiting layer between them, and the shape of the cells that made up each layer, all fruits consisted of three layers, the exocarp, the mesocarp, and the endocarp.  The thickness of each layer was different in all species. It was found that the fruiting envelope is thicker in the type Medicago polymorpha L, as the average thickness of the coat reaches (342) micrometers, and the thickness of (146.9) micrometers was recorded in the type M. monspeliaca.  As for the shapes of cells and their types, remarkable variations were recorded, as they had several shapes (oval, spherical, elliptical, semi-oval, elongated) and this makes them of taxonomic significance even between the phenotypically close types, which confirmed the current study, in addition to  Lack of anatomical studies of the fruits of wild species in Iraq.